DEVELOPING STUDENTS’ READING COMPETENCE THROUGH COGNITIVE COGNITIVE STRATEGIES - Saxatova Iroda Sunnatillayevna (Modern World Education: New Age Problems – New solutions, 2025)
Reading competence represents a fundamental dimension of second language proficiency and is closely linked to learners’ academic success. Contemporary theoretical research emphasizes that effective reading extends beyond linguistic decoding and requires the activation of cognitive strategies that facilitate constructing meaning, integrating textual information, and sustaining comprehension. This article synthesizes key theoretical perspectives on how cognitive strategies contribute to the development of reading competence, drawing on foundational models such as schema-driven processing and the Construction-Integration framework. The analysis highlights the central role of strategies such as predicting, inferencing, elaboration, and summarizing in enabling learners to process texts more efficiently and accurately. It also clarifies the distinction between automatic reading skills and deliberate cognitive operations, demonstrating that strategic engagement enhances readers’ ability to interpret, evaluate, and retain written information. The findings suggest that integrating cognitive strategy instruction into reading pedagogy can significantly support the development of higher-order comprehension abilities in EFL contexts and provide a theoretical foundation for designing cognitively informed instructional approaches.